Study on biofilm formation ability of multidrug-resistant Acinetobacter baumannii in surveillance of nosocomial infection (多重耐药鲍曼不动杆菌生物被膜形成能力在医院感染监测中的研究) - LI Kaixuan (李凯旋); DI Youhua (狄友华); ZHOU YANG (周杨); WANG XING (王幸); CHEN LEI (陈蕾); YAN Ruina (严蕊娜) (中西医结合护理)
Objective To explore the appearance of multi-drug resistant Acinetobacter baumannii in clinical infection cases in the hospital from 2018 to 2010 and its biofilm formation ability, providing a theoretical research basis for in-depth understanding of bacterial biofilm infection and its drug resistance mechanism, and providing ideas and methods for clinical prevention, control and treatment. Methods The multi-drug resistant Acinetobacter baumannii isolated from the Microbiology Room of the Second Affiliated Hospital of Xi’an Medical College from March 2018 to March 2020 was collected, and the strains were identified and tested by the automatic bacterial identification instrument VITEK-2 identification and drug sensitivity analysis system. For drug susceptibility testing, Congo red medium was used to qualitatively test the biofilm-forming ability of the selected 89 beads multi-drug resistant experimental strains. The morphological and structural characteristics of multi-drug resistant Acinetobacter baumannii biofilms established on 6-well cell culture plates were qualitatively observed by scanning electron microscope. A 96-well cell culture plate and LB culture medium were used for constant temperature culture and the in vitro multi-drug resistant Acinetobacter baumannii biofilm was constructed. Crystal violet solution staining was used to determine the absorbance value, and the formation of the multi-drug resistant experimental strain biofilm was quantitatively detected. Results Qualitative detection of Congo red medium showed a positive rate of 71. 91% (64/89). Most of the specimens were sourced from the ICU ward of the Department of Respiratory and Critical Care Medicine, accounting for 45. 31% (29/64). Most of them were alveolar lavage fluid specimens. Most of the infected people were older than 60 years old, had certain underlying diseases, stayed in the ICU for a long time, used two or more antibiotics, and had invasive procedures such as tracheal intubation/incision. Bacterial biofilm could be formed in 96-well cell culture plate at 37°C constant temperature for 72 hours. Crystal violet staining and quantitative detection of the absorbance value with a microplate reader showed that the amount of biofilm formed after 48 hours of culture was the highest, with a positive rate of 79. 78% (71/89). It was able to be used as an experimental condition for determining the biofilm formation ability of clinical multi-drug-resistant Acinetobacter baumannii. The positive multi-resistant test strains screened by Congo Red Agar medium could form bacterial biofilms on 96-well cell culture plates. Conclusion In clinical testing, multi-drug resistant Acinetobacter baumannii has strong drug resistance and is positively correlated with the ability of biofilm formation. The production of biofilm is one of the important reasons for its multi-drug resistance mechanism. The coating of pathogenic bacteria increases clinical control The difficulty of infection, the main way of transmission is contact transmission, so it is very important to do a good job in the prevention and control of nosocomial infection. (目的 研究分析医院2018年—2020年临床病原学送检标本中多重耐药鲍曼不动杆菌分离检出情况及其生物被膜的形成能力, 为深入了解细菌生物膜感染及其耐药机制提供理论研究基础, 并为临床医院感染防控与治疗提供思路与方法。方法 收集2018年3月—2020年3月西安医学院第二附属医院微生物室经VITEK-2细菌鉴定仪和药敏分析系统分离鉴定出的多重耐药鲍曼不动杆菌, 采用刚果红培养基对筛选出的89珠多重耐药实验菌株进行生物膜形成能力的定性检测, 并在6孔细胞培养板上构建多重耐药实验菌株生物膜, 使用扫描电子显微镜定性观察生物膜形态及结构特点。用96孔细胞培养板和LB培养液恒温培养构建体外多重耐药实验菌株生物膜, 结晶紫溶液染色法测定其吸光度值, 定量检测多重耐药实验菌株生物膜的形成量。结果 刚果红培养基定性检测, 阳性率达71. 91％(64/89)。标本来源大多是肺泡灌洗液标本, 以呼吸与危重症医学科ICU病房居多, 占45. 31%(29/64)。患者多以60岁以上老龄感染者, 有一定基础疾病、入住ICU时间较长、使用两种及两种以上抗菌素、且有气管插管/切开等侵入性操作。将多重耐药实验菌株在96孔细胞培养板37°C培养72 h, 结晶紫染色和酶标仪定量检测吸光度显示, 培养48 h后生物膜的形成量最高, 阳性率为79. 78％(71/89), 可作为确定临床多重耐药鲍曼不动杆菌生物膜形成能力的实验条件。在刚果红琼脂培养基上筛选出的具有多重耐药性的阳性实验菌株均可在96孔细胞培养板上形成细菌生物膜。结论 在临床体外试验中多重耐药的鲍曼不动杆菌具有很强的耐药性且与生物膜形成能力呈正相关。 生物被膜的产生是其多重耐药机制的重要原因之一, 病原菌被膜包裹增加了临床控制感染的难度, 其传播途径主要为接触传播, 因此做好院内感染的防控工作及其重要。)